The Effect of Different Taxpayer Demographics on the Comparative Importance of a Tax System’s Guiding Principles - Davies, Karen J.; Davies, Thomas L.; Carr, David L. (Journal of Accounting and Finance, 2020)
This paper reports additional findings of a 2017 study that was undertaken to determine taxpayer perceptions about the relative importance of 10 guiding principles of a good tax system. Taxpayer views are compared based on their gender, income level, education and age. The paper builds upon an earlier article, which discussed differences in taxpayer perceptions based on their political affiliation and ideological philosophy.